School Principals’ Levels of Administrative Competences based on the Perceptions of Principals and Teachers - Sabit Menteşe (Foxton Books, 2021)
This study aims to determine school principals’ level of administrative competencies according to the perceptions of teachers and principals. The study group consists of 134 teachers and 35 principals. The data of the research, which was designed in the survey model, were collected with the "School Administrators' Competences Inventory". The results revealed that school principals and teachers exhibited high levels of administrative Competencies as expected from the school principals. The opinions of the teachers and principals did not differ significantly in the comparisons according to gender, seniority, school type, and duties (teacher vs. principal). Likewise, the correlation coefficients between the administrative competence subscales were estimated above a moderate level. As a result of the research, it can be said that teachers and principals have positive views about the competencies of the school administrators. However, though the Ministry of National Education and the academic community put great emphasis on it, and a significant deal of knowledge and database has been accumulated about it; it is an important problem that school administration has not been defined as a profession in Turkey and no sustainable policy in this aspect has been developed yet